2016
DOI: 10.1242/jcs.193029
|View full text |Cite
|
Sign up to set email alerts
|

Thyroid follicle development requires Smad1/Smad5- and endothelial-dependent basement membrane assembly

Abstract: Thyroid follicles, the functional units of the thyroid gland, are delineated by a monolayer of thyrocytes resting on a continuous basement membrane. The developmental mechanisms of folliculogenesis, whereby follicles are formed by the reorganization of a non-structured mass of non-polarized epithelial cells, are largely unknown. Here we show that assembly of the epithelial basement membrane is crucial for folliculogenesis and is controlled by endothelial cell invasion and by BMP-Smad signaling in thyrocytes. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
14
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(16 citation statements)
references
References 26 publications
2
14
0
Order By: Relevance
“…The final growth and completion of morphogenesis into organized follicles in the thyroid glands of these mice are defective, resembling the loss-of-function phenotype of the proangiogenic vascular endothelial growth factor-A (Villacorte et al 2016). Thyroid glands with defective BMP signaling show defective basement membrane, and extracellular matrix proteins like laminins can rescue the developmental defect (Villacorte et al 2016). Thus, BMP signaling assists in the architectural organization of the epitheliumto-basement membrane barrier (Villacorte et al 2016).…”
Section: Thyroid Gland Developmentmentioning
confidence: 92%
See 3 more Smart Citations
“…The final growth and completion of morphogenesis into organized follicles in the thyroid glands of these mice are defective, resembling the loss-of-function phenotype of the proangiogenic vascular endothelial growth factor-A (Villacorte et al 2016). Thyroid glands with defective BMP signaling show defective basement membrane, and extracellular matrix proteins like laminins can rescue the developmental defect (Villacorte et al 2016). Thus, BMP signaling assists in the architectural organization of the epitheliumto-basement membrane barrier (Villacorte et al 2016).…”
Section: Thyroid Gland Developmentmentioning
confidence: 92%
“…Conditional expression of TGF-b1 in thyrocytes of transgenic NOD mice promotes the development of thyroid hyperplasia, and inhibits autoimmune thyroiditis that is presumably because of enhanced recruitment of regulatory T cells into the thyroid glands (Yu et al 2010). BMP signaling promotes thyroid epithelial development, as evidenced from the effects of conditional inactivation of both Smad1 and Smad5 in thyrocytes (Villacorte et al 2016). The final growth and completion of morphogenesis into organized follicles in the thyroid glands of these mice are defective, resembling the loss-of-function phenotype of the proangiogenic vascular endothelial growth factor-A (Villacorte et al 2016).…”
Section: Thyroid Gland Developmentmentioning
confidence: 99%
See 2 more Smart Citations
“…Moreover, this decrease in thyroid endothelial density negatively impacts on the organisation of epithelial cells into pre-follicular structures at E15.5 and eventually into large polarised epithelial monolayers (follicles) around birth ( 9 ). We further showed that the assembly of the basement membrane, partly controlled by endothelial cell invasion in the thyroid, was crucial for epithelial cell orientation, acquisition of polarity and in fine follicle formation ( 10 ).…”
Section: Introductionmentioning
confidence: 93%